SIMBOL-SIMBOL DALAM GUNUNGAN WAYANG KULIT JAWA - Aini Loita (Prodi Pendidikan Sendratasik FKIP UMTAS, 2019)
Puppet is a legacy of the past that has been tradition until now. Although in its development, wayang experienced changes as innovations to maintain it, but there were fixed structures that did not change, such as the form of the puppet itself, how to perform it, the structure of the gamelan, its suluk-suluk, philosophy and others. One of the Javanese shadow puppets called gunungan has many symbols of visual values ??that can be observed and interpreted as the noble heritage of traditional values. This article outlines the analysis of the visual meaning of the Javanese shadow puppet views from the point of view of the symbol of Tribuwana or Tiga Dunia, Up, Down, Middle.